Co-creating strategies to promote uptake of HIV self-testing among young adults in Mecklenburg county, North Carolina: a protocol for a pilot implementation study - Ucheoma Nwaozuru; Lindsay Miller; Laura H. Gunn; Laura H. Gunn; Laura H. Gunn; Sebastian Marin-Cespedes; Margaret Hanff; Patrick Robinson; Michael Dulin; Meghana Muralidhar; Prashant Jha; Goodness C. Mirikwe; et al. (Frontiers in Health Services)
BackgroundHIV testing is the gateway to entering HIV care and prevention services. However, HIV testing rates remain low among young adults (18–29 years old) in Mecklenburg County, North Carolina (NC), an ending the HIV epidemic (EHE) priority jurisdiction. We aim to utilize community-engaged and participatory approaches to co-create implementation strategies to promote the reach and uptake of HIV self-testing (HIVST) among young adults in the region. This study protocol outlines the phases of the project and the proposed outcomes.MethodsThe Community-engaged Approaches to Expand HIV Self-Testing among Young Adults in Mecklenburg County, North Carolina (CATEST) project will be conducted in three phases, guided by the Consolidated Framework for Implementation Research (CFIR), Community-based Participatory Research (CBPR), and Reach, Effectiveness, Adoption, Implementation, and Maintenance (RE-AIM) frameworks. The formative phase of the study, guided by CFIR, will focus on understanding the barriers, facilitators, and opportunities for implementing HIVST among young adults in Mecklenburg County, North Carolina. The second phase, guided by CBPR, will utilize participatory approaches such as crowdsourcing open calls and charrettes to co-create implementation strategies for HIVST. Then, the final pilot implementation phase, guided by CFIR and RE-AIM, will use mixed methods to evaluate the success of the co-created HIVST implementation strategies using a pre-post design. Participants in the study will complete a baseline survey and a follow-up survey immediately following intervention completion. In addition, a purposive sample of participants and representatives at the participating community organization will complete qualitative exit interviews within 1 month of intervention completion.DiscussionThis study protocol outlines the co-creation of implementation strategies, tests their feasibility, and explores preliminary effectiveness in promoting HIVST uptake among young adults in Mecklenburg County, NC. The study will yield insights on the feasibility of leveraging the capabilities of community and youth innovation to promote young adults-centered implementation strategies to advance the reach and adoption of HIVST among young adults.RegistrationRegistered on Open Science Forum-DOI 10.17605/OSF.IO/2BZWV.